Governing climate change:: urbanization, vulnerability and challenges for the northern coast of the state of São Paulo, Brazil - Martins, Rafael D’Almeida; Ferreira, Leila da Costa (Sustainability in Debate, 2011)
This paper examines the climate change vulnerability of the Northern Coast of the State of São Paulo (Litoral Norte Paulista), Brazil. Based on a literature review and a case-study encompassing the analysis of policy documents, secondary data and semi-structured interviews with policymakers and civil society representatives, it aims to provide a useful way to examine the multiple and overlapping processes of environmental, social-economic and climatic change in this region. By analyzing its vulnerability, the paper argues that the degree to which these cities are vulnerable to climate change is largely determined by the broader historic and socio-economic contextual factors. The finding indicates that the social, economic and cultural changes brought by the last four decades of intense process of urbanization, tourism exploitation and increasingly economic activities have deepened social and environmental problems, increasing the vulnerability of particular groups and the region as a whole to climate variability and change. The cross-scale nature of the problems and the cross-level interactions of these processes pose significant challenges for the governance structures and institutions on the region that fail to address the root causes of vulnerability, highlighting the municipalities’ insufficiency to address the consequences of a changing environment and climate.